E1a is an exogenous in vivo tumour suppressor. (28th July 2017) - Cimas, Francisco J.; Callejas-Valera, Juan L.; García-Olmo, Dolores C.; Hernández-Losa, Javier; Melgar-Rojas, Pedro; Ruiz-Hidalgo, María J.; Pascual-Serra, Raquel; Ortega-Muelas, Marta; Roche, Olga; Marcos, Pilar; Garcia-Gil, Elena; Fernandez-Aroca, Diego M.; et al.
Abstract: The E1a gene from adenovirus has become a major tool in cancer research. Since the discovery of E1a, it has been proposed to be an oncogene, becoming a key element in the model of cooperation between oncogenes. However, E1a's in vivo behaviour is consistent with a tumour suppressor gene, due to the block/delay observed in different xenograft models. To clarify this interesting controversy, we have evaluated the effect of the E1a 13s isoform from adenovirus 5 in vivo . Initially, a conventional xenograft approach was performed using previously unreported HCT116 and B16-F10 cells, showing a clear anti-tumour effect regardless of the mouse's immunological background (immunosuppressed/immunocompetent). Next, we engineered a transgenic mouse model in which inducible E1a 13s expression was under the control of cytokeratin 5 to avoid side effects during embryonic development. Our results show that E1a is able to block chemical skin carcinogenesis, showing an anti-tumour effect. The present report demonstrates the in vivo anti-tumour effect of E1a, showing that the in vitro oncogenic role of E1a cannot be extrapolated in vivo, supporting its future use in gene therapy approaches. Highlights: E1a blocks xenograft formation independently of the immune system status. Transgenic mice expressing E1a are refractory to DMBA/TPA skin carcinogenesis. E1a is not and in vivo oncogene. E1a exerts an anti-tumour effect in vivo .